Conditioned reinforcement can be mediated by either outcome-specific or general affective representations - Burke, Kathryn A.; Franz, Theresa M.; Miller, Danielle N.; Schoenbaum, Geoffrey (Frontiers in Integrative Neuroscience, 2007)
Conditioned reinforcers are Pavlovian cues that support the acquisition and maintenance of new instrumental responses. Responding on the basis of conditioned rather than primary reinforcers is a pervasive part of modern life, yet we have a remarkably limited understanding of what underlying associative information is triggered by these cues to guide responding. Specifically, it is not certain whether conditioned reinforcers are effective because they evoke representations of specific outcomes or because they trigger general affective states that are independent of any specific outcome. This question has important implications for how different brain circuits might be involved in conditioned reinforcement. Here, we use specialized Pavlovian training procedures, reinforcer devaluation and transreinforcer blocking, to create cues that were biased to preferentially evoke either devaluation-insensitive, general affect representations or, devaluationsensitive, outcome-specific representations. Subsequently, these cues, along with normally conditioned control cues, were presented contingent on lever pressing.We found that intact rats learned to lever press for either the outcome or the affect cues to the same extent as for a normally conditioned cue. These results demonstrate that conditioned reinforcers can guide responding through either type of associative information. Interestingly, conditioned reinforcement was abolished in rats with basolateral amygdala lesions. Consistent with the extant literature, this result suggests a general role for basolateral amygdala in conditioned reinforcement. The implications of these data, combined with recent reports from our laboratory of a more specialized role of orbitofrontal cortex in conditioned reinforcement, will be discussed.